Belief reversals as phase transitions and economic fragility: a complexity theory of financial cycles with reflexive agents: Belief reversals as phase transitions and economic fragility: A complexity theory of financial cycles with reflexive agents - Davis, John (Review of evolutionary political economy (Online), 2020)
This paper aims to contribute to the analysis of expectations and belief reversals in a evolutionary and complexity economics framework. It formulates its analysis in terms of the concept of reflexivity, drawing on the ideas regarding reflexivity in financial markets of George Soros, and lays out a model of how a financial cycle expresses a systematic pattern of interacting feedback effects. The paper develops this analysis as a complex interaction between sets of heterogeneous expectations derived from the behavior of reflexive economic agents. Positive and negative feedback phases in a cycle are distinguished and associated with boom and bust stages of that cycle. A central role is played by agents’ beliefs and judgments underlying their expectations, and how those beliefs and judgments in uncertain circumstances are changeable and subject to abrupt reversals which can manifest themselves in “Minsky moments.” The paper argues that agents’ belief reversals result from their misconceptions about causal processes in booms and upswings, a misconception that reflects their tendency to think causally in terms of negative feedback patterns rather than positive ones.